2013
DOI: 10.6117/kmeps.2013.20.4.025
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric and Pyroelectric Properties of Lead-Free Sodium Bismuth Titanate Thin Films Due to Excess Sodium and Bismuth Addition

Abstract: Pb-free ferroelectric (Na 0.5 Bi 0.5 )TiO 3 (NBT) thin films were prepared by a modified sol-gel process. Their structural, dielectric and pyroelectric properties were investigated as a function of the excess Na/Bi ratio and the annealing temperature. In the case of thin films containing no excess Na and Bi, only partial amounts of the perovskite NBT were crystallized, where the films consisted mainly of the pyrochlore phase of Bi 2 Ti 2 O 7 for annealing conditions of 600~800 o C. With increasing excess Na/Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…In case of amount of Na less than 40 %, the gelforming vaporization results in the lack of a necessary amount of Na, hence the new phase of Bi 2 Ti 2 O 7 is formed to. This observation is in a good agreement with the report of Kang et al [14]. In addition, when the Na amount in range of 10 -30 mol%, other imputity phases are observed and difficult to identify the origin of these phases.…”
Section: Methodssupporting
confidence: 92%
See 1 more Smart Citation
“…In case of amount of Na less than 40 %, the gelforming vaporization results in the lack of a necessary amount of Na, hence the new phase of Bi 2 Ti 2 O 7 is formed to. This observation is in a good agreement with the report of Kang et al [14]. In addition, when the Na amount in range of 10 -30 mol%, other imputity phases are observed and difficult to identify the origin of these phases.…”
Section: Methodssupporting
confidence: 92%
“…Kang et al found that the phase formation, ferroelectronic and insulating properties of Bi 0.5 Na 0.5 TiO 3 film synthesized by sol-gel method strongly depended on the primary ratio of Bi/Na because these elements are easy to evaporate during gelization and annealing processes [14]. However, these reports about the evaporating amount of Na during gelization,the influence of sintering temperture on the phase information and optical properties of this material have not been performed in a systematic manner.…”
Section: Figure1mentioning
confidence: 99%
“…However, the PZT often showed poor fatigue endurance with a Pt electrode and contains the highly toxic lead ion as part of its chemical composition, which acts as a major obstacle for use in practical devices [2][3][4]. Particularly, the volatile PbO in PZT is considered to pose a serious threat to human health because it is highly toxic [4].…”
Section: Introductionmentioning
confidence: 99%
“…The formation of secondary phases and oxygen vacancies lead to poor electrical and ferroelectric properties in the NaBTi thin film. Various methods, such as compositional compensation by the addition of excessive Na and Bi ions and cationic doping, have been established to obtain single-phase NaBTi and to control oxygen vacancies, respectively [2,4,16]. In fact, for Bi-based ferroelectric compounds, doping with RE metal ions has been strongly recommended as a way of controlling the leakage current and to improve the ferroelectric properties [2,9,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation